Digital Marketing Strategy in Increasing Sales of Afiza Crackers in Kendit Situbondo Village - Rasidi, Moh.; Faizah, Dzurratul (Golden Ratio of Social Science and Education, 2024)
This study aims to analyze the digital marketing strategy in increasing sales of Afiza crackers, a micro business located in Kendit Village, Situbondo. Kerupuk Afiza is a home-based product developed by Mrs. Miswa since 2019, relying on hereditary recipes and local raw materials. Previously, the business only relied on traditional marketing methods such as sales at local markets and neighborhood stalls, which led to stagnant sales growth. Through a qualitative approach, data was collected from interviews with the business owner, two employees, and four resellers. The results showed that product uniqueness and flavor consistency are the main advantages. Marketing strategies are carried out through simple social media such as WhatsApp and Facebook, although business actors still experience constraints in digital management. Product distribution was expanded through a network of resellers, overcoming the constraints of less strategic business locations. In addition, flavor diversification, affordable pricing, and internal training for employees helped maintain product quality and competitiveness. In terms of production, limited tools and dependence on the weather are challenges that need to be overcome. This study concludes that although Afiza crackers have not fully implemented digital marketing strategies optimally, the combination of personal promotion, social media utilization, and empowerment of local human resources has had a significant impact in increasing sales. Further training in digital marketing and production technology development is recommended to strengthen the competitiveness of the business in the future.